BEBERAPA FAKTOR YANG MEMPENGARUHI KEPATUHAN IBU HAMIL TERHADAP KUNJUNGAN ANTENATAL CARE DI FASILITAS KESEHATAN - Hasibuan, Khoirunnisah; Utama, Risma Putri; Isnaeny, Isnaeny; Hardiyanti, Sri (Ensiklopedia of Journal, 2025)
Abstract: The increase in maternal and child mortality is still one of the serious problems in the world of health, especially in developing countries such as Indonesia. Based on the initial survey, it is known that Kassi-Kassi Health Center is one of the health centers with the highest pregnancy rate but has not reached the target regarding ANC visits in Makassar City. The purpose of the study was to determine the relationship of several factors that influence pregnant women's compliance with antenatal care visits at health facilities. The research design used in this study was cross sectional. The research was conducted at Kassi-Kassi Health Center in November 2024. The population of pregnant women in trimester 3 who made antenatal care visits at the Kassi-Kassi Health Center in Makassar City in September 2024, totaling 115 pregnant women. The sample amounted to 50 respondents. The sampling technique used in this study was purposive sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between the parity of pregnant women (p value: 0.00) and the work of pregnant women (p value: 0.002) on antenatal care visits. It is recommended to the health center to be able to hold counseling evenly in 6 villages at the Kassi-Kassi Health Center regarding the importance of conducting antenatal care checks for the health of mothers and children.Keywords: Antenatal Care, Toddler, Parity.